Long-term follow-up of anterior thalamic deep brain stimulation in epilepsy: A 11-year, single center experience. (November 2017) - Kim, Seong Hoon; Lim, Sung Chul; Kim, Jiyeon; Son, Byung-Chul; Lee, Kyung Jin; Shon, Young-Min
Highlights: We studied to evaluate the long-term efficacy and safety of ATN DBS treatment. 11-year median seizure reduction was 70%: 13.8% seizure-free for at least 1 year. Complications including Infection, hemorrhage, lead disconnection & malposition. ATN DBS for DRE showed a good therapeutic efficacy lasted at least 11 years. Abstract: Purpose: Anterior thalamic deep brain stimulation (ATN DBS) is an emerging, effective treatment for patients with drug-resistant epilepsy, but long-term results on its efficacy and safety are lacking. To evaluate the long-term efficacy and safety of ATN DBS treatment, as well as predictors of its success, in patients with drug-refractory epilepsy (DRE). Method: We retrospectively studied clinical outcomes in 29 consecutive refractory epilepsy patients treated by a single DBS team (two neurosurgeons, four neurologists) over an 11-year period, for whom follow-up was performed for up to 137 months (mean, 74.9 months). Results: The average participant was 30.7 (±10.4) years old and had epilepsy for 19.3 (±9.0) years. The mean preoperative frequency of disabling partial or generalized tonic-clonic seizures was 27.5 (±8.6, SE) seizures a month. The median percent seizure reduction was 71.3% at 1 year, 73.9% at 2 years, and ranged from 61.8% to 80.0% over post-implant years 3 through 11 in the long-term study (overall 70% median reduction). In the 11-year study period, 13.8% (4/29) of subjects were seizure-free for at least 12 months during this time. There was only one symptomatic intracranial hemorrhage that happened during follow-up (3.4%). Infection requiring removal and later re-implantation of hardware occurred in only 1 of 30 patients (3.3%), who was subsequently excluded from our follow-up assessment. Hardware malfunction including lead disconnection occurred in 2 of 29 cases (6.9%). Revision of lead position to redeem poor clinical response was performed in 3 of 58 implanted leads (5.2%). Conclusions: ATN DBS can be an effective therapy in a variety of patients with DRE. Importantly, we provide evidence that significant therapeutic efficacy can be sustained for up to 11 years. Neurological complications were rather rare, but long-term hardware-related complications should be followed arrectis auribus.